House dust fungal communities’ characterization: a double take on the six by sixty by six project (6x60x6) - Amaro, R. (2018)
Fungi are a group microbes, that are found with particular incidence in the indoor environment. Their direct toxicity or capability of generating toxic compounds has been associated with a large number of adverse health effects, such as infectious diseases, allergies and other toxic effects. Our study aims to quantify and identify the fungal community on house dust samples collected using two different methodologies (an approach not often seen in the literature): active (vacuum cleaner bags) and passive sampling (dust settled in petri dishes).